(cis)-Jasmona como indutor de resistencia em Vigna unguiculata (L.) Walp. (Fabaceae) para o Aphis craccivora Koch 1854 (HEMIPTERA: APHIDIDAE) - Gutiérrez, Miguel Angel Martinez (2020)
Abstract Cowpea beans, Vigna unguiculata (L.) Walp. (Fabaceae), is an important crop and provides relatively inexpensive nutritious food for low-income populations in developing countries. One of the limiting factors for its production is the black aphid, Aphis Craccivora Koch 1854 (Hemíptera: Aphididae), responsible for the transmission of the mosaic virus (Cowpea aphid borne mosaic virus), CABMV. One of the tools in the integrated management of this pest is the use of semi-chemicals, resistant varieties and resistance inducers, which are environmentally friendly methods for farmers. The objective of this work was to study the mechanisms of action of the cis-Jasmone resistance inducer in the activation of the cowpea defense pathways in plants induced with CJ and submitted to infestation with black aphid. Thus, we sought to identify the VOCs of three cowpea genotypes using the genotype Vita 7 (susceptible), BRS-Guariba (resistant) and BR19 Gurgueia (tolerant) in the treatments of healthy plants (control), plants treated with cis-Jasmone ( CJ), plants infested with aphids (P) and plants treated with cis- Jasmone plus aphid (CJP), evaluate the activity or repellency of VOCs against aphids and perform the antibiosis test using different doses of cis-Jasmone. The results obtained in this project are: in the GC-MS analyzes it was possible to observe a variation in the VOCs emissions in the plants treated with CJ and CJP. The plants of the CJ treatment showed the emission of the compounds farnesol, β-caryophyllene, 6-methyl-5-hepten-2-one, citronelal, sabinene, camphor and isomentol, these compounds have shown repellent activity in other cultures. The VOCs of all plants were subjected to multivariate analyzes where formations of 3 groups were observed, according to the similarity of the VOCs emitted. In the free choice test, extracts from the control plants of the BR19 Gurgueia genotype were attractive to insects, while VOCs released by these genotypes after infestation showed repellency for the insects tested in the bioassays. The extracts of the plants Guariba and Gurgueia after the application of cis-Jasmone were significantly repellent to the black aphid. In the tests of preference without a choice, the three doses of cis-Jasmona (50 g / ha, 75 g / ha, 100 g / ha) induced antibiosis-like resistance in the plants of the Vita 7 genotype (susceptible) in the semi-field test, and the dose of 75 g / ha showed a lower number of live insects (adults and nymphs), when compared with the other doses and with the control treatment plants. Our results reveal that the cowpea plants induced with cis-Jasmone can activate their defense mechanisms against the aphid A. craccivora exerting effects of anti-poisoning and antibiosis resistance. Keywords: Elicitor; Cópia; Semiochemicals; Volatile organic compounds, Antixenosis, Antibiosis.